iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Meekan, Mark; Austin, Christopher M.; Tan, Mun H.; Wei, Nu-Wei V.; Miller, Adam; Pierce, Simon J.; Rowat, David; Stevens, Guy; Davies, Tim K.; Ponzo, Alessandro; Gan, Han Ming (Frontiers in Marine Science, 2017)
The whale shark (Rhincodon typus) is an iconic and endangered species with a broad distribution spanning warm-temperate and tropical oceans. Effective conservation management of the species requires an understanding of the degree of genetic connectivity among populations, which is hampered by the need for sampling that involves invasive techniques. Here, the feasibility of minimally-invasive sampling was explored by isolating and sequencing whale shark DNA from a commensal or possibly parasitic copepod, Pandarus rhincodonicus that occurs on the skin of the host. We successfully recovered mitochondrial control region DNA sequences (~1,000 bp) of the host via DNA extraction and polymerase chain reaction from whole copepod specimens. DNA sequences obtained from multiple copepods collected from the same shark exhibited 100% sequence similarity, suggesting a persistent association of copepods with individual hosts. Newly-generated mitochondrial haplotypes of whale shark hosts derived from the copepods were included in an analysis of the genetic structure of the global population of whale sharks (644 sequences; 136 haplotypes). Our results supported those of previous studies and suggested limited genetic structuring across most of the species range, but the presence of a genetically unique and potentially isolated population in the Atlantic Ocean. Furthermore, we recovered the mitogenome and nuclear ribosomal genes of a whale shark using a shotgun sequencing approach on copepod tissue. The recovered mitogenome is the third mitogenome reported for the species and the first from the Mozambique population. Our invertebrate DNA (iDNA) approach could be used to better understand the population structure of whale sharks, particularly in the Atlantic Ocean, and also for genetic analyses of other elasmobranchs parasitized by pandarid copepods.